Perceptions and attitudes of postgraduate students toward the flipped classroom model: case study at Vinh University, Vietnam - Huong Thi Nguyen; Le Van Vinh; Thai Thi Hong Lam; Nhi Thi Nguyen (International Journal of Evaluation and Research in Education (IJERE), 2026)
Teaching using the flipped classroom model (FCM) is one of the methods of organizing teaching that combines (blended learning) electronic learning methods (e-learning) with traditional teaching and learning methods. The research aims to understand the perceptions and attitudes of postgraduate students at Vinh University towards the flipped classroom and analyze the benefits and difficulties that students encounter. When teaching according to FCM, thereby proposing solutions to improve efficiency when teaching according to this model. The research was conducted using a combination of qualitative and quantitative methods. Quantitative data were obtained from the participation of 121 postgraduate students in teacher training. Qualitative data was taken from the interview results of seven students who experienced the flipped classroom. Results from the survey show that the majority of students have a positive attitude toward learning in the FCM. Research also shows that the FCM positively impacts students’ attitudes toward the course through the benefits it brings. Students participating in the survey also shared the difficulties they encountered when studying in the FCM and gave some suggestions to improve the effectiveness of applying this model in the future.